1984
DOI: 10.1080/02640418408729693
|View full text |Cite
|
Sign up to set email alerts
|

Physiological efficiency of constant power output at varying pedal rates

Abstract: The study investigated the absolute and relative (% maximal) physiological demands of constant power output at three pedal rates chosen to incorporate the range used by racing cyclists. Following the assessment of maximal exercise capabilities utilizing a recently developed racing cycle ergometry system, ten highly trained racing cyclists undertook a randomized sequence of work bouts at low (70.0 ± 1.1), medium (94.8 ± 0.8) and high (126.5 ± 1.1) pedal rates per minute at constant power output under an unloade… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

1989
1989
2004
2004

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 17 publications
(30 reference statements)
0
6
0
Order By: Relevance
“…Our values for work efficiency on the cycle ergometer were close to those reported by other authors. A number of studies have reported work efficiency to be in the range 20-26% (Andersen and Saltin, 1985;Asmussen and BondePetersen, 1974;Davis et al, 1982;Henry and Demoor, 1950;Merrill and White, 1984;Stuart et al, 1981;Suzuki, 1979).…”
Section: Discussionmentioning
confidence: 99%
“…Our values for work efficiency on the cycle ergometer were close to those reported by other authors. A number of studies have reported work efficiency to be in the range 20-26% (Andersen and Saltin, 1985;Asmussen and BondePetersen, 1974;Davis et al, 1982;Henry and Demoor, 1950;Merrill and White, 1984;Stuart et al, 1981;Suzuki, 1979).…”
Section: Discussionmentioning
confidence: 99%
“…Powers et al (1984) have shown that gross efficiency increases as a function of power output, but decreases as a function of speed of movement in arm cranking. Merrill and White (1985) showed a decreasing metabolic economy with increasing pedalling rate in simulated racing cycling. A reasonable extension of these works would be to examine the riders' response to variations in cadence and power output by examining the associated pedal forces.…”
Section: Introductionmentioning
confidence: 92%
“…Banister and Jackson, 1967;Seabury et al, 1977;Merrill and White, 1985). Coast and Welch (1985) have shown that for equivalent power outputs, there is a minimal energy expenditure, as measured by oxygen uptake, associated with a specific pedal rate (rev min~1).…”
Section: Introductionmentioning
confidence: 99%
“…One can maintain a constant power output even when speed is varied. However, despite an unchanging power output, a change in speed and thus force has been shown to affect many physiological responses including metabolic efficiency, [1][2][3][4][5][6][7] oxygen deficit, 8 lactate threshold, 9 and aerobic capacity. 8 Much of the pertinent literature has been related to movement economy or athletic performance.…”
mentioning
confidence: 99%